2022
DOI: 10.1186/s12913-022-07725-9
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of infertility treatment and distribution of expenditures overtime in France: a self-controlled pre-post study

Abstract: Background Recent cost studies related to infertility treatment have focused on assisted reproductive technologies. None has examined lower-intensity infertility treatments or analyzed the distribution of infertility treatment expenditures over time. The Purpose of the study was to analyse the size and distribution of infertility treatment expenditures over time, and estimate the economic burden of infertility treatment per 10,000 women aged 18 − 50 in France from a societal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…As observed by the field investigators of the present study, exercise among infertile women is one of the recommendations of the doctors as a part of their treatment protocol specifically for the reduction of PCOS and other related infertility issues. Some intervention and prospective studies have also demonstrated that lesser exercise results in higher levels of perceived stress [ 25 , 26 ]. Further, clinical trials have demonstrated that exercise is an effective method for reducing perceived stress, stress symptoms, and quality of life [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed by the field investigators of the present study, exercise among infertile women is one of the recommendations of the doctors as a part of their treatment protocol specifically for the reduction of PCOS and other related infertility issues. Some intervention and prospective studies have also demonstrated that lesser exercise results in higher levels of perceived stress [ 25 , 26 ]. Further, clinical trials have demonstrated that exercise is an effective method for reducing perceived stress, stress symptoms, and quality of life [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some intervention and prospective studies have also demonstrated that lesser exercise results in higher levels of perceived stress [ 25 , 26 ]. Further, clinical trials have demonstrated that exercise is an effective method for reducing perceived stress, stress symptoms, and quality of life [ 25 ]. Among the fertile group, physically active women were found to be more stressed, which could be due to workload, the pressure of household chores, or other family or children-related issues [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80 million people and about one-fifth of couples during their lifetime are affected by infertility worldwide [ 1 , 2 , 3 ]. In addition, infertility has a significant economic impact and is a multilayered stressor associated with anxiety, depression, and dysfunctions in marital and sexual relationships that affect quality of life [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The economic burden is also high, largely due to ART techniques 6 . A study in France recently analysed the size and distribution of expenditure related to infertility treatment over time, and estimated the economic burden of infertility treatment in France 7 . One of the main results, in addition to quantifying the economic burden of infertility management (estimated at 6996 [95% CI: 5755–8237] euros over a 3.5‐year follow‐up period), was demonstrating the significant share of health care expenses related to drugs, especially in the first two semesters of infertility management (47% and 35% of expenses, respectively).…”
Section: Introductionmentioning
confidence: 99%